2017
DOI: 10.1111/faam.12131
|View full text |Cite
|
Sign up to set email alerts
|

Examining the process of performance measurement system design and implementation in two Italian public service organizations

Abstract: In the last two decades, the adoption of new public management (NPM) practices in the public sector has increased as public sector organizations seek to improve efficiency, effectiveness and public accountability. We present case study findings of a NPM initiative to implement balanced scorecard (BSC) performance measurement systems in two Italian public sector organizations. This study considers the question of whether the BSC development process can be effectively translated into the public sector context. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 67 publications
2
50
0
Order By: Relevance
“…The discussion of moving away from NPM toward a new public governance “paradigm” (Holmgren Caicedo, Mårtensson, & Tamm Hallström, ; Osborne, , ; Wiesel & Modell, ) touches upon this, but fails to recognize the inherent difference of understanding efficiency (Hyndman & Liguori, ). It is furthermore common that the role of accounting is not fully recognized in such settings (Bracci, Maran, & Inglis, ; Mennicken, ; Pallott, ). This means that the debate on whether or how much NPM has improved efficiency in the public services will continue as long as the intentions and justifications of NPM reforms are vague.…”
Section: Knowledge Gained From Existing Studies On Npmmentioning
confidence: 99%
See 2 more Smart Citations
“…The discussion of moving away from NPM toward a new public governance “paradigm” (Holmgren Caicedo, Mårtensson, & Tamm Hallström, ; Osborne, , ; Wiesel & Modell, ) touches upon this, but fails to recognize the inherent difference of understanding efficiency (Hyndman & Liguori, ). It is furthermore common that the role of accounting is not fully recognized in such settings (Bracci, Maran, & Inglis, ; Mennicken, ; Pallott, ). This means that the debate on whether or how much NPM has improved efficiency in the public services will continue as long as the intentions and justifications of NPM reforms are vague.…”
Section: Knowledge Gained From Existing Studies On Npmmentioning
confidence: 99%
“…As shown in Table , a total of 56 articles were published between 1997 and 2016. From these 56 articles, we found 18 studies (32%) that report on findings from the Nordic countries and more than 50% of the published articles discuss NPM in countries outside United Kingdom and USA (cf., Blomgren, ; Bracci et al., ; Christopher & Leung, ; Czarniawska & Mazza, ). This means that the one‐sided perspective identified and discussed above may perhaps not be representative for accounting research focusing on NPM.…”
Section: Knowledge Gained From Existing Studies On Npmmentioning
confidence: 99%
See 1 more Smart Citation
“…A major stream of the domain theory on PMS design takes a systems approach (Bedford, Malmi, & Sandelin, 2016;Bracci, Maran, & Inglis, 2017;Malmi & Brown, 2008). An example of the application of systems theory in a qualitative, in-depth, single case study can be found in Friis, Hansen, and Vámosi (2015), who studied the interdependence between elements of control systems.…”
Section: Using Domain Theory To Assess the System As A Success Or Faimentioning
confidence: 99%
“…If they are not, the PMS will fail to provide internal transparency. Thus, our research is not a quantitative contingency theoretical study of 'fit'/'misfit' (Drazin & Van De Ven, 1985), but rather an exploratory systems theory analysis (Bracci et al, 2017;Friis et al, 2015 are other examples of this) of how PMS components produce transparency by examining whether the PMS measures both efficiency and effectiveness.…”
Section: Using Domain Theory To Assess the System As A Success Or Faimentioning
confidence: 99%